A southern Māori perspective on stories of Polynesian polar voyaging. (15th November 2021) - Anderson, Atholl; O'Regan, Tipene; Parata-Goodall, Puamiria; Stevens, Michael; Tau, Te Maire
Abstract: As Ngāi Tahu (southern Maori), we take issue with widespread reference in scholarly publication to Polynesian voyagers reaching the Antarctic, an idea that originated in the translation of Rarotongan traditions in the nineteenth century. Analysis of those indicates that they contain no plausible reference to Antarctic seafaring. Southern Māori interests have extended into the Subantarctic Islands for 800 years but there is no reference to Antarctica in our historical traditions. Our archaeology and history document a southern boundary to Māori occupation at Port Ross (Auckland Islands), despite habitable islands existing further south. We think it is very unlikely that Māori or other Polynesian voyaging reached the Antarctic.